A 2D free-standing film-inspired electrocatalyst for highly efficient hydrogen production. Issue 24 (7th June 2017) - Gao, Jian; Cheng, Zhihua; Shao, Changxiang; Zhao, Yang; Zhang, Zhipan; Qu, Liangti
Abstract : A high electrocatalytic performance free-standing film based on molybdenum carbide nanoribbons between N-doped graphene nanolayers was developed. Abstract : The development of self-supporting binder-free catalysts is of great significance for the practical application of the electrocatalytic hydrogen evolution reaction (HER). In this work, we report a rationally assembled two dimensional (2D) free-standing film based on 1D molybdenum carbide nanoribbons between nitrogen doped graphene nanolayers (Mo2 C nanoribbon/N-G). Due to multichannel and expeditious charge and mass transport, the integrated Mo2 C nanoribbon/N-G film exhibits a remarkable HER performance with a low onset potential of 84 mV ( vs. the RHE), a small Tafel slope of 57 mV dec −1, and an overpotential of 162 mV ( vs. the RHE) to reach a current density of 10 mA cm −2, superior to most transition metal based free-standing catalysts reported previously. This work provides a great advance for designing and fabricating cost-effective, applicable catalysts for hydrogen evolution and water splitting.